If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4y + -10) = 8(2y + -7) Reorder the terms: 6(-10 + 4y) = 8(2y + -7) (-10 * 6 + 4y * 6) = 8(2y + -7) (-60 + 24y) = 8(2y + -7) Reorder the terms: -60 + 24y = 8(-7 + 2y) -60 + 24y = (-7 * 8 + 2y * 8) -60 + 24y = (-56 + 16y) Solving -60 + 24y = -56 + 16y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16y' to each side of the equation. -60 + 24y + -16y = -56 + 16y + -16y Combine like terms: 24y + -16y = 8y -60 + 8y = -56 + 16y + -16y Combine like terms: 16y + -16y = 0 -60 + 8y = -56 + 0 -60 + 8y = -56 Add '60' to each side of the equation. -60 + 60 + 8y = -56 + 60 Combine like terms: -60 + 60 = 0 0 + 8y = -56 + 60 8y = -56 + 60 Combine like terms: -56 + 60 = 4 8y = 4 Divide each side by '8'. y = 0.5 Simplifying y = 0.5
| -70=-4x-5(-2x+8) | | (2/5)+y=3 | | 3a+20=2a+26 | | 6.8(x-2)=-0.2x+28.4 | | 187=3x+7(4x-3-3) | | 2x^2+x^2=400 | | 3(7x+5)=120 | | 4b=2b+24 | | 3x^2+46x+49=0 | | 7x-17=3x+9 | | 7(2+x)=42 | | 5x-17=3x+7 | | 6x-9x+5=x-2+7 | | 3x+5=7x | | 3x^2+x^2=100 | | 2(x-4)+3x=7 | | 3(2+4x)=6 | | 3x-8-7x=2x+8+2x | | 60(x+20)+3x=180 | | 8=2(4-3x)+6 | | y-8=(x-8) | | 60+20x+3x=180 | | 2x^2(x^2-3x+5)=0 | | 5(x+1)=-60 | | 24-3x=2x+4 | | (x-1)-3=0 | | -4.1-4x=12.7 | | 9+5x=x+9 | | 18x+2y+16+3x-5y-2= | | 5(x+1)=11 | | (4x+9)(2x-7)=0 | | 4+x+6x=18 |